Ethical practices and implications in distance learning [ - Demiray, Ugur; Sharma, Ramesh C. (Hershey, PA : Information Science Reference, 2009)
"This book provides ethical insight into the world of e-learning through case studies that elucidate the issues through real-world examples"--Provided by publisher.
"Premier reference source"--Cover
Description based on print version record
Includes bibliographical references (p 333-376) and index
Keywords: Distance education -- Moral and ethical aspects